Human exposure and mass balance distribution during procymidone application in horticultural greenhouses - Fitó Friedrichs, Gretel Alejandra (2020)
The purpose of this study was to analyze the impact of procymidone application in periurban horticultural greenhouses, especially on workers (applicators and assistants) and soil and plastic mulching, when mechanically pressurized application systems were employed. The mean Potential Dermal Exposure (PDE) was measured using the Whole Body Dosimetry technique. The PDE for the applicators was 188 mL h−1 ± 103 mL h−1, and 14.7 mL h−1 ± 6.3 mL h−1 for the assistants. In the first case, the most exposed body sections were the upper right and left (46.8 mL h−1 ± 23.4 mL h−1; 47.0 mL h−1 ± 23.5 mL h−1) and lower (20.8 mL h−1 ± 10.4 mL h−1; 17.3 mL h−1 ± 8.7 mL h−1) legs, while in the case of assistants, hands and legs were the most impacted limbs. Regarding the Margin of Safety (MOS) during the mix and load stage, two of three pesticide preparations resulted unsafe, while for the applicators, six of six spraying operations were unsafe. For the assistants, five of five operations were safe, but three of them were close to the safety limit. Procymidone distribution between drift (0.03% ± 0.07 %), applicator (0.20% ± 0.15 %), polyethylene mulching (8.5% ± 4.5 %) and soil (3.0% ± 1.1 %) was determined with respect to the total pesticide applied. Procymidone soil impact was also evaluated using Eisenia andrei behavioral tests, finding positive correlations between procymidone application and avoidance and reproduction tests.